Maintaining customer lifetime value through cross selling offers with shopping vouchers gimmick in the insurance industry by using logistic regression and decision tree - Adi Chandra; Hendra Achmadi (Enrichment : Journal of Management, 2023)
This research is conducted in the life insurance industry in order to help the company to extend and maintain customer lifetime value. A statistical model will be built using Logistic Regression (LR) and Decision Tree (DT) methods so that the company can find/use the right model of input variables (independent variables) those later determines/increases the probability/chance of the take up rate of the cross-selling offers: whether YES (accept the given offer) or NO (reject the given offer). The impact of shopping vouchers as gimmick will be seen as well. This research is using primary data in the form of data of active life insurance policyholders who currently have a term life product where the policy is approaching the maturity date (3 months before the maturity date). Policyholders, hereinafter referred to as clients, consist of custo500 clients with the following demographic profiles: Gender: Male/Female; Age: 45-60 years, Marital Status: Single, Married, Divorced; Have made a claim: Yes/No, Policy Age: 5, 10 and 15 years, Annual Premium Value: 20 - 54 Million; Communication Channels in distributing the offer: SMS, Email, Mail (specifically Mail: only given to clients over 55 years of age); The rupiah value of the vouchers offered: IDR 250k, 350k and 500k. The data was obtained from the results of cross sell activities carried out by the company from one of the cross-sell initiative batches. The statistical model will be built using the logistic regression and decision tree method with Visual Studio Code - Python software. Responds to offers in the form of Yes or No are withdrawn after 30 calendar days after the offer is made. From the results of the research, the Logistic Regression model give result with Accuracy: 0.95; Precision: 0.75; Recall: 0.66 and F1-score: 0.70. The Decision Tree model give result with Accuracy: 0.93; Precision: 0.84; Recall: 0.81 and F1-score: 0.69. The two models provide almost similar performance. Novelty of this research shows claims experience play dominant role in determining the result of the cross sell on top of the voucher gimmick offer